2024
DOI: 10.3390/ijerph21010100
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Interaction Time and Verbal Engagement with Personal Voice Assistants on Alleviating Loneliness among Older Adults: An Exploratory Study

Changmin Yan,
Kate Johnson,
Valerie K. Jones

Abstract: Background: Loneliness in older adults is a critical issue that negatively affects their well-being. The potential of personal voice assistant (PVA) devices like Amazon’s Alexa Echo in reducing loneliness is an emerging area of interest, but it remains under-researched. Objective: this study aims to investigate the effect of interaction time and verbal engagement with PVA devices on reducing loneliness among older adults living alone. Method: In this experiment, individuals aged 75 and older (n = 15), living a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Additionally, VAs can facilitate communication between older adults and others, especially those with visual or hand function impairments ( Kowalski et al, 2019 ). It also found that VAs can serve as social companions to some extent ( Corbett et al, 2021 ; Yan et al, 2024 ). Lastly, VAs can also assist in daily health activities such as health tracking, medication management, and meal planning, which could support the elderly’s daily lives ( Nallam et al, 2020 ; Schlomann et al, 2021 ; Yan et al, 2024 ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Additionally, VAs can facilitate communication between older adults and others, especially those with visual or hand function impairments ( Kowalski et al, 2019 ). It also found that VAs can serve as social companions to some extent ( Corbett et al, 2021 ; Yan et al, 2024 ). Lastly, VAs can also assist in daily health activities such as health tracking, medication management, and meal planning, which could support the elderly’s daily lives ( Nallam et al, 2020 ; Schlomann et al, 2021 ; Yan et al, 2024 ).…”
Section: Introductionmentioning
confidence: 97%
“…It also found that VAs can serve as social companions to some extent ( Corbett et al, 2021 ; Yan et al, 2024 ). Lastly, VAs can also assist in daily health activities such as health tracking, medication management, and meal planning, which could support the elderly’s daily lives ( Nallam et al, 2020 ; Schlomann et al, 2021 ; Yan et al, 2024 ).…”
Section: Introductionmentioning
confidence: 97%
“…The hands-free and eyes-free interaction with SVA provides older individuals with immediate and intuitive benefits, especially when considering physical challenges ( 1 , 3 ). The ease of use can be critical, as more interaction with NLP-powered SVAs may lead to greater health benefits ( 18 ). However, this also brings about new difficulties in understanding their verbal interactions with the SVA.…”
Section: Introductionmentioning
confidence: 99%